Self-empowerment - Lloyd, Sam R. (Crisp Pub. Menlo ParkUS, 1992)
Explains the terminology and principles of empowerment and provides opportunity for self-evaluation. Teaches how to build self-esteem; how to deal with people more effectively, and, how to improve management skills.